The Influence of Task Complexity, Self-Efficacy, and Audit Risk on Auditor Performance at Public Accounting Office (Kap) in Makassar City - Rezki Amanda; Haliah Haliah; Andi Kusumawati (International Journal Labs, 2023)
This study aims to examine the effect of task complexity, self-efficacy and audit risk on auditor performance at KAP in Makassar City. The data in this study were obtained from each KAP in Makassar City who were willing to be respondents. This study uses primary data by conducting direct research in the field by giving a questionnaire/statement sheet to 31 respondents. The data analysis method used is multiple linear regression analysis. The results showed that: 1) Task complexity has a negative and significant effect on auditor performance, 2) Self-efficacy has a positive and significant effect on auditor performance, 3) Audit risk has a negative and significant effect on auditor performance, and 4) Task complexity, self-efficacy, audit risk simultaneously have a significant effect on auditor performance.